EVALUASI AWAL TIGA JENIS POHON MULTIGUNA ALTERNATIF SUMBER HIJAUAN PAKAN DI LAHAN KERING LEMBAH PALU - Rosmiaty Arief; Tarsono Tarsono; Andi L. Amar (Agroland: Jurnal Ilmu-ilmu Pertanian, 2008)
The preliminary research had been conducted to gather information on nutritive values of various plants such as kayu jawa (Lannea coramandelica), mengkudu (Morinda citrifolia), and kelor (Moringa oleifera) to be used as alternative feeds for ruminant. It was expected that the research could generate recommendation for the suitability of those plants as the sources of ruminant ration, new research plan on the comprehensive nutritive values of the plants, and agronomic tests and their procedure in dry land farming systems.  Three replicates of leave samples of 3 development phases (old leaves, well developed leaves, and young leaves along with branches) were taken from the three plant species. Therefore, the number of samples was 27. An Atomic Absorption Spectrophotometer was employed to analyze proxymat and mineral (Ca and P) content of the leaves. The research result showed that : (a) there was no interaction effect between the plant species and the leave development, (b) the content of all leave nutrients were affected by the plant species except that of fat, whereas the leave development significantly affected only the Calcium content, (c) based on the leave nutrient composition contained, M. oleifera and M. citrifolia could be used as alternative feed particularly for calcium and phosphorous supplies for ruminant in the Palu Valley to replace L. coramandelica which have been more popular, (d) As M. citrifolia and M. oleifera contained sufficiently high BETN level, these plants can be used as an alternative feed that can be mixed with other types of feeds containing non protein nitrogen (NPN), thus enhancing the overall feed nutrition. The research recommend that there is a need to proceed the research on L. coramandelica, M. citrifolia, dan M. oleifera as the source of feed for ruminant in the aspect of biological tests such as preferency and digestibitlity either in-sacco or in-vivo.  New experiments relating to growth measurements, productive and reproductive levels will comprehensively add the biological values of the three plants as the sources of ruminant feed.